Considerations for Proper Use of Hyaluronidase in the Management of Hyaluronic Acid Fillers - Yi, Kyu-Ho; Wan, Jovian; Yoon, Song Eun (Plastic and reconstructive surgery. Global open, 2025)
Effective management of complications from hyaluronic acid (HA) fillers is crucial in aesthetic medicine. This article examined the role of hyaluronidase in addressing adverse effects associated with HA fillers, such as nodules, vascular occlusions, and excessive volume. It highlights the enzyme's ability to degrade HA, thereby resolving issues that may arise from filler treatments. The discussion includes practical aspects of using hyaluronidase, such as recommended dosing, injection techniques, and potential risks. The benefits of hyaluronidase, including its rapid action in dissolving problematic fillers and its role in improving patient outcomes, are explored. The article also addresses limitations and safety considerations to provide a comprehensive understanding of hyaluronidase in the context of filler complications. By offering insights into the application and effectiveness of hyaluronidase, this article aimed to enhance practitioners' ability to manage HA filler-related issues effectively and ensure optimal results in aesthetic procedures.